Thymol action on cells and tissues of the synganglia and salivary glands of Rhipicephalus sanguineus sensu lato females (Acari: Ixodidae) - Matos, Renata Silva [UNESP]; Daemon, Erik; de Oliveira Monteiro, Caio Márcio; Sampieri, Bruno Rodrigues [UNESP]; Marchesini, Paula Barroso C.; Delmonte, Camila; Camargo-Mathias, Maria Izabel [UNESP] (Elsevier, 2019)
Thymol is a monoterpene present in plants of the families Lamiaceae, Verbenaceae and Apiaceae. Despite its proven acaricidal activity, little is known about the mechanism of action of thymol in ticks. Thus, the aim of this study was to perform a morpho-histochemical analysis of the synganglion and salivary glands of partially engorged females of the brown dog tick, Rhipicephalus sanguineus sensu lato (s.l.), exposed to thymol at different concentrations. Five groups were established: Control Group I (distilled water), Control Group II (ethanol 30%), Group III (thymol 1.25 mg/mL), Group IV (thymol 2.5 mg/mL) and Group V (thymol 5.0 mg/mL). The females were exposed to the treatments by the immersion method and subsequently kept in a climatic chamber (27 ± 1 °C and relative humidity 80 ± 10%) for five days. After this period, the synganglion and salivary glands were removed, and the hematoxylin/eosin morphological technique was applied. The von Kossa staining method with counterstaining neutral red was performed on the salivary glands. The results showed that females exposed to thymol had damaged synganglia, with pyknotic nuclei and vacuoles in the cortex and subperineurial regions, as well as rupture of the neural lamellae. The salivary glands showed type I acini with a dilated lumen. Cells with extremely vacuolated cytoplasm and fragmented nuclei were observed in type II and III acini. Type II acini of the females exposed to thymol revealed different calcium staining when compared to the Control Groups I and II. We therefore conclude that the salivary glands and synganglion are subject to changes in morphology and calcium levels when exposed to thymol at concentrations of 1.25, 2.5 and 5.0 mg/mL, demonstrating that this monoterpene has acaricidal potential on partially engorged females of R. sanguineus (s.l.)
Keywords: Calcium; Control; Histopathology; Monoterpene; Rhipicephalus sanguineus; Thymol